Предмет: Алгебра,
автор: ВласМихайлов
Упростите выражение:
а)(а-3)(a+2)-(a-1)во второй степени=
б)3х(х+8)-(4-х)(4х+х)=
Ответы
Автор ответа:
0
а)(а-3)(a+2)-(a-1)²=a²-3a+2a-6-(a²-2a+1)=a²-a-6-a²+2a-1=a-7
б)3х(х+8)-(4-х)(4+х)=3x²+24x-(16-x²)=3x²+24x-16+x²=4x²+24x-16=4(x²+6x-4)
б)3х(х+8)-(4-х)(4+х)=3x²+24x-(16-x²)=3x²+24x-16+x²=4x²+24x-16=4(x²+6x-4)
Похожие вопросы
Предмет: Математика,
автор: annarnaut2207
Предмет: Обществознание,
автор: sufianovalilia5
Предмет: Музыка,
автор: ksenijasustrova
Предмет: Химия,
автор: irinabax